Measuring employment and job quality in agrifood systems: Accounting for backward and forward linkages - Corong, Erwin; Gautam, Madhur; Martin, Will; Vos, Rob (International Food Policy Research Institute, 2025)
As the agricultural transformation associated with economic development proceeds, the economic fulcrum of the agrifood system moves from primary production to nonfarm activities, such as input supply, food processing, food services, and wholesale and retail trade. Traditional measures of farm employment and value added (or GDP) represent a shrinking share of the agrifood system’s total contribution. Better quantification is important not only to appreciate the role of agrifood system transformation in broader economic development, but also to inform policies that create more and better-quality jobs and accelerate structural transformation in developing economies.